Functionalized Carbon-Nanotube Sheet/Bismaleimide Nanocomposites: Mechanical and Electrical Performance Beyond Carbon-Fiber Composites - Cheng, Qunfeng; Wang, Ben; Zhang, Chuck; Liang, Zhiyong (Small (Weinheim an der Bergstrasse, Germany), 2010)
Since their discovery in 1991, carbon nanotubes (CNTs) have been considered as the next‐generation reinforcement materials to potentially replace conventional carbon fibers for producing super‐high‐performance lightweight composites. Herein, it is reported that sheets of millimeter‐long multi‐walled CNTs with stretch alignment and epoxidation functionalization reinforce bismaleimide resin, which results in composites with an unprecedentedly high tensile strength of 3081 MPa and modulus of 350 GPa, well exceeding those of state‐of‐the‐art unidirectional carbon‐fiber‐reinforced composites. The results also provide important experimental evidence of the impact of functionalization and the effect of alignment reported previously on the mechanical performance and electrical conductivity of the nanocomposites. Sheets of millimeter‐long multi‐walled carbon nanotubes (CNTs) with stretch alignment and epoxidation functionalization are used to reinforce bismaleimide (BMI) resin, which results in composites with a very high tensile strength of 3081 MPa and modulus of 350 GPa. These values well exceed those of the state‐of‐the‐art unidirectional carbon‐fiber‐reinforced composites.